From Publications of the Difficult Years of Soviet Psychiatry (quotes and comments) - Yu. A. Aleksandrovsky (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article presents excerpts from the documents of the past of domestic psychiatry. Their analysis allows, with the help of primary sources, to assess the difficult period of the middle of the last century in the development of biological science, scientific and practical psychiatry in our country. The intertwining of ideological, pseudoscientific, personal and career interests at that time, as in many areas of science, pushed aside the problems of creative scientific developments and created for many professionals an atmosphere of distrust, suspicion, and discredit of leading specialists.